Komposit Berpenguat Serat Resam Dengan Matrik Polyester Sebagai Bahan Alternatif Peredam Suara - Zakaria, Zakaria; Napitupulu, Robert; Pranandita, Nanda (Politeknik Negeri Lhokseumawe, 2024)
Resam is a type of fern or fern that usually grows in shady and humid areas. This plant has not been used as a raw material for making sound absorbers, even though resam is found in the Bangka Belitung Islands Province area so that the raw material is easy to obtain. The purpose of this research is to determine composites with resam fibre reinforcement as an alternative soundproofing material. Making sampels using hand lay-up method and research design using full factorial method. The process variables in this study are the volume fraction of 5%: 95%, 10%: 90%, 15%: 85% and the length of NaOH immersion for 60, 90, 120 minutes and the testing frequency of 125Hz, 500 Hz, and 4000Hz. Based on the results of this study, the highest overall frequency sound absorption coefficient was obtained in sample no. 6, with a volume fraction of fibre and matrix of 15% : 85% and 90 minutes of NaOH immersion of α = 0.243. While the lowest overall frequency sound absorption coefficient value is in sample no 3, with a volume fraction of fibre and matrix of 15% : 85% and 60 minutes of NaOH immersion of α = 0.193. So the composite with resam fibre reinforcement based on ISO 11654 can be used as an alternative sound absorbing material.